Arterial-hypertension in the elderly - Franco, RJD; Christovan, J. C.; Gut, Ana Lúcia [UNESP]; Tucci, PJF (Moreira Jr Editora Ltda, 1992)
The authors review the epidemiology, the etiological factors, the effect of the treatment in the evolution of the cardiovascular disease in arterial hypertension in elderly, and the use of angiotensin-converting-enzyme inhibitors such as a treatment option.